Synthesis and Antimicrobial Activity of Some Thiazolidinone Derivatives from 2-Methyl, 8-hydroxy Quinoline - Sunil Kumar Chaitanya, P.; Ishwar Bhat, K.; Subrahmanyam, E.V.S. (Asian Journal of Chemistry, 2010)
A series of thiazolidinone derivatives were synthesized from 2-methyl, 8-hydroxy quinoline. Schiff bases were prepared by condensation of hydrazide of quinoline moiety with different aromatic aldehydes (3a-3i). Cyclocondensation of Schiff bases with thioglycollic acid in presence of anhydrous zinc chloride yielded a series of thiazolidinones (4a-4i). The structures of the synthesized compounds have been established by IR, 1H NMR and mass spectra.The compounds have been screened for their antibacterial and antifungal activities.